The correlation between left atrial appendage morphology and thromboembolic risk in atrial fibrillation - Li, Chengyi; Wang, Yaoji; Xu, Buyun (Frontiers in Stroke, 2025)
Atrial fibrillation (AF) is the most common cardiac arrhythmia and a major cause of ischemic stroke. Between 91% and 100% of cardiogenic thrombi are in the left atrial appendage (LAA), and the morphology of the LAA is closely associated with the formation of LAA thrombus (LAAT). This review provides a detailed discussion of the anatomy of the LAA, the epidemiology, and the diagnosis of LAAT. It focuses on analyzing the role of LAA morphology in blood stasis, morphological abnormality, and hypercoagulable states. Accurate evaluation of the morphology of the LAA can assist with risk stratification in patients with AF. The commonly used LAA morphological evaluation indicators must be more comprehensive and objective. Recently, new imaging protocols allow for LA morphological remodeling and fibrosis assessment, which has been demonstrated to correlate with assessing the individual's risks of thromboembolic events and practical imaging of patients with LAAT.